(untitled) (Sains Humanika, 2015)
Terengganu State Government set a vision to make "Terengganu a Fully Developed State by Year 2020." Expectations are amortized through the implementation of programs and public projects in line with the Ninth Malaysia Plan (2006-2010) and Tenth (2011-2015). State Economic Development Corporation (SEDC) is an agency of the state government have a role and responsibility to help and provide a platform for students to apply the knowledge of entrepreneurship through direct involvement in secondary schools. Secondary school students who attended the Program Tunas Niaga realize how important they are to involved in the field of entrepreneurship. Five predictive factors such as finance, role model, barriers, social identity and entrepreneurial skills to influence their intention to involved in the field of entrepreneurship. Goodness of employment entrepreneurship as an intermediary link between the four predictive factors such as finance, role model, barriers and entrepreneurial skills with a intention to involved in the field of entrepreneurship. The importance of predictive factors such as finance, role model, barriers and entrepreneurial skills can be used by the authorities to encourage and foster intention to involved in entrepreneurship career among secondary school students who participate in the Program Tunas Niaga.